PEMBUATAN MOL (MIKRO ORGANISME LOKAL) DI DESA SUMBER AGUNG BENGKULU UTARA - Parwito Parwito; Eko Fransisko (Fakultas Pertanian, 2025)
This Community Service activity aims to provide understanding and training to the people of Sumber Agung Village, North Bengkulu, on the production of Local Microorganisms (MOL) as an alternative solution for environmentally friendly agriculture. MOL is expected to improve soil quality, enhance soil microbiota structure, and reduce dependence on chemical fertilizers. The implementation method used a participatory approach that combines theory and hands-on practice, where the community was taught how to produce MOL using natural materials readily available in their surroundings. This activity was carried out on September 6, 2024, with a focus on the application of MOL in agricultural processes to increase production and environmental sustainability. The results of this activity indicate that the community of Sumber Agung Village has gained an understanding of the concept of MOL production and its application in their agriculture. Furthermore, they acquired practical skills that allow them to reduce the use of chemical fertilizers and transition to more environmentally friendly farming practices. In conclusion, this activity successfully had a positive impact by enhancing the knowledge and skills of the community in producing and utilizing MOL. Moving forward, it is hoped that the community can apply sustainable farming principles to support the economic and environmental welfare of their village